2016
DOI: 10.1111/1346-8138.13315
|View full text |Cite
|
Sign up to set email alerts
|

Bull's eye dermatoscopy pattern at bacillus Calmette–Guérin inoculation site correlates with systemic involvements in patients with Kawasaki disease

Abstract: For the past decades, although the rash at the bacillus Calmette-Guérin (BCG) inoculation site has been recognized as a diagnostic clue in Kawasaki disease, the present study is the first known one attempting to characterize BCG inoculation by dermatoscopy in Kawasaki disease and correlate the grade of BCG reaction with systemic involvement. Thirty-four patients diagnosed with Kawasaki disease by pediatric specialists were enrolled. We performed detailed history taking, laboratory examination, physical examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…(14) It has been hypothesised that the T-cell system has a significant role in facilitating vascular endothelial cell injury in KD. (15)(16)(17) A recent Taiwanese study in 2016 has attempted to better characterise these changes via dermatoscopy, (11) but further prospective studies of BCG site reactions (either quantified by dermatoscopy or histopathological examination) in patients with KD and other febrile illnesses would be useful to further evaluate this association and its significance. Of note, seven out of nine patients with non-KD febrile illnesses with BCG site reaction or induration were infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(14) It has been hypothesised that the T-cell system has a significant role in facilitating vascular endothelial cell injury in KD. (15)(16)(17) A recent Taiwanese study in 2016 has attempted to better characterise these changes via dermatoscopy, (11) but further prospective studies of BCG site reactions (either quantified by dermatoscopy or histopathological examination) in patients with KD and other febrile illnesses would be useful to further evaluate this association and its significance. Of note, seven out of nine patients with non-KD febrile illnesses with BCG site reaction or induration were infants.…”
Section: Discussionmentioning
confidence: 99%
“…(8)(9)(10) A recent Taiwanese study in 2016 characterised and graded the reaction at the BCG site in KD via dermatoscopy. (11) It identified bull's-eye pattern under dermatoscopy as a good clinical clue for systemic involvement, i.e. abnormal elevation of liver enzymes and cardiac complications (dilatation of the coronary arteries).…”
Section: Introductionmentioning
confidence: 99%
“…In patients who have received Bacillus Calmette-Guerin vaccine, erythema, crusting and induration of the skin at the site of vaccination are considered strong specific indicators of KD [13]. Tseng et al [18] recently attempted to correlate the grade of BCG reaction to the severity of systemic involvement in Kawasaki disease. They reported that severe induration in the form of target lesions was associated with highest elevation of liver enzymes, and the risk of coronary artery dilatations and milder induration in the form of a faint rash or a homogenous white area were associated with lesser degree of systemic inflammation in KD.…”
Section: Diagnosismentioning
confidence: 99%
“…They reported that severe induration in the form of target lesions was associated with highest elevation of liver enzymes, and the risk of coronary artery dilatations and milder induration in the form of a faint rash or a homogenous white area were associated with lesser degree of systemic inflammation in KD. These investigators also indicated that the target lesions could, therefore, even serve as biomarkers of clinical severity of KD [18]. …”
Section: Diagnosismentioning
confidence: 99%
“…In addition to standard diagnostic criteria, KD patients may experience a variety of nonspecific clinical features, including uveitis, aseptic meningitis, abdominal pain, gallbladder hydrops, rash at the bacillus Calmette-Guérin inoculation site, impaired liver function, hypoalbuminemia, and anemia [15,17,18,19]. Of these, anemia is the most common clinical feature in KD patients and is thought to have a more prolonged duration of active inflammation [20,21,22,23].…”
Section: Anemia In Patients With Kawasaki Diseasementioning
confidence: 99%